Effect of Health Education Intervention on Knowledge Regarding Sexually Transmitted Infections among Rural Female School Going Adolescents - Akter, Khadiza; Alam, Ummul Khair; Dastider, Sathi; Antora, Zahra Mustafiz; Obayed, Trifa; Nurunnabi, Mohammad (Medicine Today, 2026)
Introduction: Adolescent girls, particularly in rural areas, are vulnerable to sexually transmitted infections (STIs) and often have limited or inaccurate knowledge. Health education interventions play a crucial role in improving awareness and promoting preventive behaviors. Aims and Objectives: To evaluate the effect of a structured health education intervention on STI-related knowledge among rural female school-going adolescents. Materials and Methods: A quasi-experimental, one-group pre-test/post-test study was conducted among 140 Class 9 female students from two rural girls’ high schools in Tangail, Bangladesh, between January and December 2023. Data were collected using a semi-structured, self-administered questionnaire covering socio-demographics and knowledge on STI types, causative agents, transmission, symptoms, complications, prevention, and treatment. The intervention comprised a classroom-based session and a handbook in Bangla. Knowledge was reassessed two weeks post-intervention. Results: The majority of respondents (72.9%) were aged 13–15 years; with a mean age of 15.1±0.8 years (range 13–17). Baseline knowledge was low, with widespread misconceptions about STI types, causative agents, transmission, symptoms, complications, and prevention. Post-intervention, significant improvements were observed across all domains (p<0.001). Total median knowledge scores increased substantially, and the proportion of participants with good knowledge rose markedly, demonstrating the intervention’s effectiveness in enhancing STI-related awareness. Conclusion: Structured health education significantly improves knowledge of STIs among rural adolescent girls. Integrating comprehensive STI education into school curriculam can empower adolescents to adopt preventive behaviors and reduce the risk of STIs and related health issues. Medicine Today 2026, Vol.38 (1): 85-89